An Exploratory Study On The Out-Of-School Literacy Practices Of Malaysian Chinese Undergraduates In A Malaysian University - Vivien, Chee Pei Wei (2013)
The interest in academic literacy research has led many second language literacy researchers to overlook other types of literacy practices that L2 learners engaged in beyond the classrooms. Literacy practices such as reading and writing are closely related (Badariah, Yah & Nor Adeena, 2011) and the undergraduates who do not read in their free time faced problems when they write assignments and thus perform poorly in tests. These reluctant readers (Ambigapathy, 2000) found themselves not only unable to cope with rigorous academic demands at the university level, but also in situations beyond the school.